An unanticipated case of heterotopic pregnancy - Chawla, Shalini; Abulhassan, Nashwa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The objective of this article is to raise awareness of an increase in incidence of spontaneous heterotopic pregnancies which may be secondary to tubal damage caused by underlying pelvic inflammatory disease or may occur without any risk factors. A high index of clinical suspicion coupled with increased diagnostic sonographic accuracy and meticulous follow-up will aid appropriate management of both intra and extra uterine components of a heterotopic gestation. This is a case of unanticipated heterotopic pregnancy that was initially diagnosed as ectopic pregnancy. Intra-uterine pregnancy was subsequently detected post operatively during follow up. Follow-up of all salpingectomies through a urine pregnancy test may aid in picking up cases of heterotopic pregnancy that were missed at initial presentation either clinically or on ultrasound. Increased vigilance will improve the management of a complex condition that poses a diagnostic dilemma.